Formation of informational and digital competence of secondary school students in laboratory work in physics - Oleksandr O. Martyniuk; Oleksandr S. Martyniuk; Ivan O. Muzyka (Academy of Cognitive and Natural Sciences, 2021)
The article deals with the formation of informational and digital competence of high school students. First and foremost, the existing digitalization strategies for society already approved in the world and in Ukraine, including the implementation of STEM education and the Digital Agenda, are considered. On the other hand, attention is paid to the inconsistency of the level of ownership and frequency of use of digital technologies with the requirements of these initiatives. The concept of informational and digital competence is analyzed in detail. Existing publications identify key components, skills and competencies required to achieve this competence. A survey is conducted to better understand the current situation. One of the tasks is to determine the level of use of digital information in the classroom by teachers and in students' preparation at home. The second task was to show how developing students' informational and digital competence can be done by active introduction of existing software and hardware in the educational process in physics, in particular, a laboratory workshop. The example of laboratory work carried out in educational institutions shows how modern software can be used to analyze the movement of bodies and determine the physical characteristics of this movement. The concrete ways of performing laboratory work, analyzing its results and drawing conclusions are given. It is in the combination of existing teaching practices with modern gadgets, specialized and general programs that the basic way of forming informational and digital competence is seen. Further ways of modernization and improvement of described methods for increasing the level of information and digital competence are proposed.